Analisis Manipulasi laporan keuangan dan Dampaknya terhadap Kelangsungan Usaha Perusahaan - Shyafira Riyadi; Rafika Yasmine; Keyla Andrea Putri Sumarsono; Vinadia Vinadia; Alfin Toffler Sofyan; Louis Promedicano Turnip; Rafhy Bahana Sati; Arry Eksandy (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Financial statement manipulation remains a significant issue in the business environment and can affect the quality of information used in decision-making processes. This practice may take various forms, including improper revenue recognition, asset overstatement, cash flow manipulation, and the concealment of liabilities. This study aims to analyze the forms of financial statement manipulation and examine their impact on a company's going concern. The research employs a qualitative approach using a literature review method by examining relevant journals, academic articles, and other scholarly publications. The findings indicate that financial statement manipulation is generally driven by pressures to achieve performance targets, weak internal controls, and inadequate corporate oversight. The cases reviewed demonstrate that such practices can lead to serious consequences, including a decline in investor confidence, liquidity problems, financial losses, regulatory sanctions, and threats to business sustainability. The study also highlights the importance of transparency, accountability, and the implementation of good corporate governance in preventing financial statement manipulation. Therefore, companies should strengthen their internal control systems and improve the quality of financial reporting to maintain credibility and support long-term business sustainability.